Plasma von Willebrand Factor Is Elevated Hyperacutely After Mild Traumatic Brain Injury - Rachel Thomas; Cillian E. Lynch; Jeff Debad; Christopher Campbell; Onyinyechi Chidomere; Joseph Kilianski; Kan Ding; Christopher Madden; Danielle K. Sandsmark; Ramon Diaz-Arrastia; Joshua W. Gatson (Neurotrauma Reports, 2023)
Each year in the United States, ?2.7 million persons seek medical attention for traumatic brain injury (TBI), of which ?85% are characterized as being mild brain injuries. Many different cell types in the brain are affected in these heterogeneous injuries, including neurons, glia, and the brain vasculature. Efforts to identify biomarkers that reflect the injury of these different cell types have been a focus of ongoing investigation. We hypothesized that von Willebrand factor (vWF) is a sensitive biomarker for acute traumatic vascular injury and correlates with symptom severity post-TBI. To address this, blood was collected from professional boxing athletes (n?=?17) before and within 30?min after competition. Plasma levels of vWF and neuron-specific enolase were measured using the Meso Scale Discovery, LLC. (MSD) electrochemiluminescence array-based multi-plex format (MSD, Gaithersburg, MD). Additional symptom and outcome data from boxers and patients, such as the Rivermead symptom scores (Rivermead Post Concussion Symptoms Questionnaire [RPQ-3]), were collected. We found that, subsequent to boxing bouts, there was a 1.8-fold increase in vWF levels within 30?min of injury (p?<?0.0009). Moreover, fold-change in vWF correlates moderately (r?=?0.51; p?=?0.03) with the number of head blows. We also found a positive correlation (r?=?0.69; p?=?0.002) between fold-change in vWF and self-reported post-concussive symptoms, measured by the RPQ-3. The receiver operating curve analysis of vWF plasma levels and RPQ-3 scoring yielded a sensitivity of 94.12% and a specificity of 76.5% with an area under the curve of 83% for boxers after a fight compared to the pre-bout baseline. This study suggests that vWF is a potential blood biomarker measurable in the hyperacute period after blunt mild TBI. This biomarker may prove to be useful in diagnosing and monitoring traumatic vascular injury.